2014
DOI: 10.1089/jamp.2012.0992
|View full text |Cite
|
Sign up to set email alerts
|

Aerosolized Albuterol Sulfate Delivery under Neonatal Ventilatory Conditions: In Vitro Evaluation of a Novel Ventilator Circuit Patient Interface Connector

Abstract: The use of the VC connector increased the delivery of albuterol sulfate and resulted in a PSD profile at the patient interface that is more consistent with the PSD profile of the selected nebulizer when compared with SoC. This VC connector may be a useful, new approach for the delivery of aerosolized medications to neonates requiring positive pressure ventilatory support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 16 publications
0
20
0
1
Order By: Relevance
“…(11)(12)(13)(14) This extremely low delivery efficiency has been consistently demonstrated based on in vitro experiments (13,14) and animal models, (11,13,15) and in humans. (16) Newer vibrating mesh and ultrasonic nebulizers have significantly increased lung delivery efficiency of aerosols for ventilated infants to a value of approximately 10% in some cases.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…(11)(12)(13)(14) This extremely low delivery efficiency has been consistently demonstrated based on in vitro experiments (13,14) and animal models, (11,13,15) and in humans. (16) Newer vibrating mesh and ultrasonic nebulizers have significantly increased lung delivery efficiency of aerosols for ventilated infants to a value of approximately 10% in some cases.…”
mentioning
confidence: 93%
“…However, this approach may not be practical for modifying the wye connector where a 90°change in flow direction is required. In a recent study by Mazela et al, (12) a redesigned wye, referred to as the VC connector, was shown to increase emitted dose (ED) in a premature neonate in vitro model. As an alternative approach, Longest et al…”
mentioning
confidence: 99%
“…The system considered in this study delivers humidity through the nebulization of an aqueous solution to avoid dehydrating the airways (Ari and Fink 2015). Using a heated and humidified line, Mazela et al (2014) delivered 6.6% of a nominal AS dose to the end of the Y-connector in a mechanical ventilation system; however, an ETT was not considered. This system used a novel VC connector to bypass bias flow and improve delivery of a jet nebulizer providing a drug delivery rate of 2.9 μg/min (Mazela et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A macaque animal model of a ventilated infant was used to demonstrate a lung delivery efficiency of 12.6 – 14% of the aerosolized dose through a 3 mm infant endotracheal tube (ETT) using a VMN synchronized with inspiration and without ventilator bias flow (Dubus et al, 2005). Using a jet nebulizer in an in vitro model of a ventilated premature infant, with a new connector to separate nebulizer and ventilation gas bias flow, Mazela et al (2014) increased albuterol sulfate delivery efficiency from 1% or less through the commercial Y-connector to a maximum of approximately 7% with the improved connector, before the ETT or mask. Additional aerosol losses are known to occur in the infant ETT, which can have an internal diameter as small as 2.5 mm.…”
Section: Introductionmentioning
confidence: 99%
“…6). 72 The low-deadspace connector has 2 different paths for the gas provided by the ventilator and the aerosol. The device lacks a oneway valve system that would prevent the practitioner from having to break the circuit when the nebulizer connections are removed.…”
Section: Special Conditionsmentioning
confidence: 99%